Ramularia mali strains isolated from petroleum product-contaminated soil are capable to grow on multiple aromatic compounds - Watumesa Agustina Tan; Helen Surya Teja; Stephanie STEPHANIE (Society for Indonesian Biodiversity, 2020)
Abstract. Tan WA, Teja HS, Stephane. 2020. Ramularia mali strains isolated from petroleum product-contaminated soil are capable to grow on multiple aromatic compounds. Biodiversitas 21: 3590-3595.  Aromatic compounds are present as a complex mixture in the environment, some of which are toxic and carcinogenic in humans and animals. In this study, we reported the first instance of arthroconidial yeast growth on more than one aromatic compound. Yeasts were isolated from soil surrounding gas stations and screened for growth on phenol, followed by qualitative growth testing on chlorobenzene, aniline, toluene, 2-nitrotoluene, benzoate, and naphthalene. Pure isolates identity and phylogeny were determined based on the ITS region. All isolates grew on phenol and benzoate, but none grew on naphthalene. Aside from the inability to grow on naphthalene, SR8 grew on other tested aromatics, while SR3 showed similar growth ability except on 2-nitrotoluene. Growth on 2-nitrotoluene was observed for PPS3, PB4, SR1, SR6, and SR8, a phenotype that has yet been reported in yeasts thus far. All isolates shared 99.81-100% similarity and were phylogenetically clustered with the arthroconidial yeast Ramularia mali CBS 129581, despite that some of them were morphologically different and had varying capability to grow on tested aromatics. Therefore, ITS sequences cannot be used to differentiate Ramularia mali up to the strain level. Overall, we demonstrated the diverse potential of yeast strains in reducing aromatic compound contamination.